Bilobed tongue base associated with multiple branchial anomalies. Issue 3 (29th March 2021) - Konstantinidou, Sevasti; Wyatt, Michelle; Butler, Colin; Frauenfelder, Claire
Abstract : A bilobed tongue base was identified in an infant with multiple other head, neck and cardiac congenital anomalies. This anatomical variation of the posterior tongue is rare, with only two other cases identified in the literature. We report a case of a 5-month-old boy with a bilobed posterior tongue incidentally identified during workup for cardiac surgery.